A digital tool to design structurally feasible semi-circular masonry arches composed of interlocking blocks. (September 2019) - Casapulla, C.; Mousavian, E.; Zarghani, M.
Highlights: The sliding resistance of an interlocking block is larger than a conventional one. The relation of interlocking shapes and sliding resistance is found heuristically. Limit analysis is extended to include non-isotropic sliding resistance. Two optimization methods find the thinnest arch with interlocking blocks. Finite element analysis is used to validate the accuracy of the proposed approach. Abstract: This work deals with a digital tool to design stable semi-circular masonry arches composed of interlocking blocks which are kept together by interlocking connectors on their faces. These blocks, comparing to conventional blocks, increase the sliding resistance and reduce the workmanship. However, current digital tools were developed mostly to design arches with conventional blocks. The proposed tool tries to fill this gap by addressing the work in three stages. First, a heuristic method is developed to define the relationships between the geometry of an interlocking face and the sliding resistance. Then, a structural analysis procedure is developed based on limit analysis and a heuristic method to define the stability condition of the arch. Finally, optimization algorithms are developed to find the thinnest arch by means of two minimization strategies dealing with the relationship between the sliding resistance of the blocks and the geometry of the interlocking faces, differently. The algorithms consider some control points on a given thrust line and automatically adjust them to minimize the thickness, while the stability condition checks the structural feasibility during the geometry adjustment. To evaluate the accuracy of the proposed heuristic method, the results obtained with FE analysis are used for comparison.